Photo-crosslinked adhesive hydrogel loaded with extracellular vesicles promoting hemostasis and liver regeneration - Xia, Wuzheng; Lai, Guanzhi; Li, Yichuan; Zeng, Cong; Sun, Chengjun; Zhang, Pinzhe; Zhu, Guanghao; Li, Leping; Wu, Linwei (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatectomy is an effective surgical method for the treatment of liver diseases, but intraoperative bleeding and postoperative liver function recovery are still key issues. This study aims to develop a composite hydrogel dressing with excellent hemostatic properties, biocompatibility, and ability to promote liver cell regeneration. The modified gelatin matrix (GelMA, 10%) was mixed with equal volumes of sodium alginate-dopamine (Alg-DA) at concentrations of 0.5%, 1%, and 2%. Then a cross-linking agent (0.1%) was added to prepare different composite hydrogels under UV light, named GelMA/Alg-DA-0.5, GelMA/Alg-DA-1 and GelMA/Alg-DA-2, respectively. All the prepared hydrogel has a porous structure with a porosity greater than 65%, and could be stabilized in a gel state after being cross-linked by ultraviolet light. Physicochemical characterization showed that the elastic modulus, water absorption, adhesion, and compressibility of the composite hydrogels were improved with increasing Alg-DA content. Furthermore, the prepared hydrogel exhibits in vitro degradability, excellent biocompatibility, and good hemostatic function. Among all tested groups, the group of GelMA/Alg-DA-1 hydrogel performed the best. To further enhance its application potential in the field of liver regeneration, adipose-derived mesenchymal stem cell exosomes (AD-MSC-Exo) were loaded into GelMA/Alg-DA-1 hydrogel. Under the same conditions, GelMA/Alg-DA-1/Exo promoted cell proliferation and migration more effectively than hydrogels without extracellular vesicles. In conclusion, the prepared GelMA/Alg-DA-1 composite hydrogel loaded with AD-MSC-Exo has great application potential in liver wound hemostasis and liver regeneration.